Multiple stationary solutions to gkp equation in a bounded domain (2002)
In this paper, we study the existence of multiple stationarysolutions of Generalized Kadomtsev-Petviashvili (Abbr. GKP) equation in a bounded domain with smooth boundary and for superlinear nonlinear term f(u) = L|u|p-2u + |u|q-2u  where 1